Clinical Study to Evaluate the Efficacy of Katphaladi Yoga on Pratishyaya w.s.r. to Allergic Rhinitis - Budihal, Shivakumar N; Pujar, Bhavani V (International Research Journal of Ayurveda & Yoga, 2022)
Background & Objectives: Pratishyaya (Allergic Rhinitis) is one of the commonest and frequently observed ailments in school going children, though seems simple but affects the regular activities. Being the most common allergic condition, acute Allergic Rhinitis affects people of all ages. In wealthy societies, it is observed that 20 to 40% of children suffer from Allergic Rhinitis. Hence the present study is intended to evaluate the efficacy of katphaladi yoga in the treatment of Pratishyaya in pediatric practice. Methods: A sample size of 30, diagnosed cases of Allergic Rhinitis, between the age group of 5 to 15 years were selected from the O.P.D. of SJG Ayurveda Medical College and hospital, camps and other referrals. Katphaladi yoga was given to the study group in a dose of 4 to 14 masha three times a day along with honey after food for 21 days. Detailed case Performa was prepared and observations were recorded and graded. Results: Results obtained after the clinical trial was analyzed statistically and all the observations were subjected to creative discussions. The final results showed that after 21 days of the treatment complete cure was observed in 30 patients and showed improvement in the clinical features. Interpretation & Conclusion: The study showed that katphaladi yoga was found effective in relieving the symptoms of Pratishyaya in children within the duration of 14 to 21 days. The present study has revealed the scope for conducting more researches in the disease Pratishyaya and the drug katphaladi yoga for its standardization.